Сучасні методи захисту навколишнього природного середовища від забруднень - Полозов, М. О. (ХНУРЕ, 2023)
The definition of the concept of «environmental pollution» and «methods of environmental protection» is determined in the work. The classification of sources of biosphere pollution is given. Technological and organizational-technical methods are analyzed.